Bubble strategy - A practical solution to return to regular life in the intertwined era of vaccine rollouts and virus mutation - Shen, Y.; Huo, D.; Yu, T.; Wang, Q. (China CDC Weekly, 2022)
For a long time, vaccination and herd immunity were considered to be the magic solution for controlling coronavirus disease 2019 (COVID-19). However, the emergence of new variants altered people`s expectations and prolonged the pandemic duration, especially the Omicron strain with substantially increased transmissibility and decreased vaccine efficacy. Therefore, we are in urgent need of a practical solution to resume regular life to some extent, while mitigating COVID-19 risks in the tight race between vaccine rollouts and virus variation. This commentary proposed that bubble strategy (or closed loop management), utilized in Tokyo 2020 Olympic Games and to be implemented in Beijing 2022 Winter Games, could serve as a novel technique of non-pharmaceutical interventions in coping with such a situation.